Analisa Keandalan Sistem Distribusi 20kv di PT. PLN (Persero) Rayon Kudus Kota Menggunakan Metode Section Technique - Mohammad Rexy Hanif; Titiek Suheta (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2020)
This study was made with the aim of calculating the reliability index of the 20 kV distribution system in APJ Kudus on KDS2 feeders, with a network length of 21.267 km and 5207 subscribers. Using the section technique method, which is a method that performs reliability evaluation by breaking the system into smaller parts, so that the possibility of errors can be minimized, and the time required is shorter. The calculation results show that the SAIFI value is 4.2705 times / year and the SAIDI value is 6.81167 hours / year. The SAIFI value is not in accordance with the SPLN standard which is 3.2 times / year, this is due to too long air ducts, external disturbances (rain, lightning, wind), and internal disturbances (human factors of equipment). However, the SAIDI value is in accordance with the SPLN standard, namely 21 hours / year